2022
DOI: 10.1037/ser0000446
|View full text |Cite
|
Sign up to set email alerts
|

When the edges blur: A future psychiatrist’s perspectives on attention-deficit/hyperactivity disorder.

Abstract: A graduating medical student and incoming psychiatry resident reflects on his diagnosis of attentiondeficit/hyperactivity disorder (ADHD) and his treatment for this condition. He also examines the impacts of ADHD and stimulant medication on his career, education, and personal life, as well as the impacts of individual and systemic mental health stigma on mental health care providers as prosumers. Impact StatementThrough personal narrative, a soon-to-be psychiatrist discusses his own diagnosis of and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…First, it is possible that a significant number of medical residents and practicing physicians with a confirmed diagnosis of ADHD do not report having this diagnosis out of fear of being stigmatized or scrutinized by colleagues or supervisors, or because of concern about legal or licensing ramifications. 38,39 Second, many medical residents and practicing physicians, despite https://doi.org/10.2147/AMEP.S398196…”
Section: Prevalence and Consequences Of Adhd In Medical Learners And ...mentioning
confidence: 99%
See 3 more Smart Citations
“…First, it is possible that a significant number of medical residents and practicing physicians with a confirmed diagnosis of ADHD do not report having this diagnosis out of fear of being stigmatized or scrutinized by colleagues or supervisors, or because of concern about legal or licensing ramifications. 38,39 Second, many medical residents and practicing physicians, despite https://doi.org/10.2147/AMEP.S398196…”
Section: Prevalence and Consequences Of Adhd In Medical Learners And ...mentioning
confidence: 99%
“…42,43 Fourth, as with many mental health conditions, significant inter-and intra-individual variability affects assessment of severity and functional impairment of ADHD symptoms, 44 and many medical residents and practicing physicians, prior to medical training, may have compensated for ADHD symptoms by relying on strong intellectual ability, the flexibility of teachers/professors, the support of significant others, and selected areas of study or activities that either provide a level of structure protective against academic, athletic, or social floundering, or are sufficiently void of tight deadlines and/or the need to regularly prioritize or multi-task that goals are achieved successfully despite the presence of inattentive symptoms. 38,40 These compensatory mechanisms then become challenged when the volume and complexity of material to be learned and applied increase dramatically during medical training. 38,44,45 Finally, although varying across studies, reported prevalence rates of ADHD in medical students 27,28,[30][31][32] are comparable to rates in the general adult population, making a precipitous drop (on the order of 10-15 times less) in such rates among residents and practicing physicians difficult to reconcile.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations
“…The last article is from the perspective of a student. Klein (2022) discusses his experience of living with Attention Deficit Hyperactivity Disorder (ADHD) as a medical student and future psychiatrist. The tension between focused discipline and constant distraction had long been a part of his life, but became an issue when his education became much more challenging as a medical student.…”
Section: Empiricalmentioning
confidence: 99%